Pengaruh Management Etika dalam Lingkungan PIAUD Sekolah Tinggi Agama Islam Ibnu Ruysd Kotabumi - Ahmad Mulyadi; Fanny Akmal Fathir; Purnama Purnama; Meilisa Sajdah (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This research aims to examine the influence of ethical management on the learning environment in Early Childhood Education (PIAUD). Good ethical management is thought to be able to create a positive, safe learning environment and support children's holistic development. The research method used is a quantitative method with a survey design. The population of this study were all teachers and parents of students at PIAUD Husnul Amal Kotabumi. Samples are taken randomly from the population., Data was collected using a questionnaire consisting of questions about ethical management and the learning environment. Data analysis was carried out using descriptive statistics and linear regression to test the effect of ethical management on the learning environment. The research results show that ethical management has a positive and significant influence on the learning environment in PIAUD. Teachers who consistently apply ethical values ​​in teaching and interacting with students succeed in creating a learning atmosphere that is more comfortable, safe and supports children's development. These findings indicate that good ethical management is an important factor in creating a conducive learning environment in PIAUD., This research suggests that PIAUD managers implement clear ethics policies and carry out strict supervision to ensure their implementation. Apart from that, training for teachers regarding the importance of ethics in education is also recommended to improve the quality of the learning environment.